Kajian Tingkat Pelayanan Bus TMB (Trans Metro Bandung) Studi Kasus : Koridor 2 Cicaheum – Cibeureum - Popon Dini; Furi Sari Nurwulandari (Jurnal Planologi Unpas, 2017)
The study is to assess or identify existing condition by comparing to the minimum service standards as seen from the attributes or benchmarks that have been established as well as identifying the perception of passengers against the attributes of bus services Trans Metro Bandung the attributes of security, safety, comfort, accessibility / ease , costs, equity and regularity, so that it can formulate recommendations bus service performance improvement Trans Metro Bandung especially on korior 2. in this study, the data is in getting through the primary survey with observation and distribution of questionnaires on the bus and the secondary surney literature review, policy and studies related agencies. The data is then analyzed using qualitative descriptive analysis method. The findings of the study that the number of stop does not comply with the conditions of land use and activity that is seen from the level of importance and satisfaction are mapped in importance performance analysis that the reply contained in the lower quadrant are the attributes of safety, comfort and safety. If linked between the importance and priority repairs of passenger satisfaction then the main thing is the attribute of security, safety and comfort, which is important perceived by passengers. Recommended study as an input for the operators and the government in improving the performance of services as a TMB bus mass transit Bandung is to improve services that are considered bad judgment that the security attributes, attributes such as safety and comfort attributes stop condition.